Supporting Women in Renewing Uzbekistan is a Privilege of Public Policy - Bobobekova Nargiza Ismatullaevna (Genius Journals, 2023)
This article is based on the reforms of the modernization period in Uzbekistan, which emphasizes that the interests of the people are the highest goal and, based on this goal, to increase the state's attention to women, their participation, prestige and place in state and societyThe importance of normative documents protecting the interests of women, their implementation in practice, the existing problems among women. A number of scientific literature, articles, legislation and works of the President have been used to cover the content of the article.
Keywords: rights; interests; women; decrees